Vision System for a Kuka Kr-5 Industrial Manipulator - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2019)
In this article, we present the design of a vision system to take objects without previous knowledge. It is considered that these objects do not have a certain position. The manipulation will be carried out by an industrial robot Kuka KR 5, which does not have a vision system, so a Microsoft Kinect camera is used, as well as the PCA (Principal Component Analysis) algorithm to estimate the position and orientation of the objects within the robot s workspace. Among the tasks to be developed is the communication between the camera and the manipulator, the integration of additional components such as; ROS (Robot Operating System), Open CV, Solidworks and MatLab-SimMechanics. In the first stage, the design of the system as whole is presented. In a following work, the manipulative task (pick and place) is carried out with the manipulator robot. © 2019 IEEE.